A sensitive and selective HPLC method for estimation of lamotrigine in human plasma and saliva: application to plasma-saliva correlation in epileptic patients - Mallayasamy, Surulivel Rajan; Arumugam, Karthik; Jain, Tarun; Rajakannan, Thiyagu; Bhat, Krishnamurthy; Gurumadhavrao, Padma; Devarakonda, Ramakrishna (Arzneimittelforschung, 2010)
A sensitive and selective high performance liquid chromatographic (HPLC) method was developed and validated for estimation of lamotrigine (CAS 84057-84-1) in human plasma and saliva. The chromatographic separation was achieved with a reversed phase column and a mobile phase consisting of acetonitrile and 20 mM ammonium acetate buffer pH 6.5 (30:70) with a flow rate of 1 mL/min. The calibration curve was linear within the working range for both plasma and saliva. The validated method has been successfully applied for a study of lamotrigine in human plasma and saliva to establish the correlation between these two matrices. A scatter plot of plasma versus salivary lamotrigine concentrations showed a good linear relationship between them (Pearson correlation coefficient, r = 0.6832, p < 0.001).
Keywords: Antiepileptic drug; CAS 84057-84-1; HPLC method; Lamotrigine, pharmacokinetics, plasma-saliva correlation